Frequency and prognostic significance of incidental prostate cancer at radical cystectomy: Results from an international retrospective study. Issue 11 (November 2017) - Malte, Rieken; Kluth, Luis A.; Kaushik, Dharam; Boorjian, Stephen A.; Abufaraj, Mohammad; Foerster, Beat; Rink, Michael; Gust, Kilian; Roghmann, Florian; Noldus, Joachim; Vordos, Dimitri; Hagiwara, Masayuki; et al.
Abstract: Objectives: To analyze the frequency of incidental prostate cancer (PC) at radical cystoprostatectomy (RC) for urothelial carcinoma of the bladder (UCB) and its association with survival outcomes in an international cohort. Patients and methods: In this retrospective study, we included 2114 who underwent RC and lymphadenectomy for UCB between 1976 and 2012 male patients from seven institutions. Univariable and multivariable Cox regression models addressed the association of incidental PC with cancer-specific mortality and overall mortality after RC. Results: Overall, incidental PC was found in 513 (24.3%) patients with the lowest frequency in a Japanese center (23/164, 11.2%) and the highest frequency in a North American center (122/325, 37.5%), respectively (p < 0.001). Within a median follow up of 27 months (IQR: 50 months), 20 patients (3.9%) were diagnosed with biochemical recurrence (BCR) and none of the patients died of PC. PC pathological tumor stage was more advanced in patients experiencing BCR (p < 0.001). In multivariable Cox regression analyses adjusted for standard clinicopathologic features, incidental PC was not associated with cancer-specific (HR: 1.11, 95% CI: 0.91–1.35, p = 0.30) or overall mortality (HR: 1.06, 95% CI: 0.83–1.35, p = 0.65). Conclusions: Incidental PC at RC for UCB is a frequent event. However, the majority of PC cases are well-differentiated and organ-confined. Presence of incidental PC shows significant geographic differences. The risk of BCR after incidental PC is low and incidental PC is not associated with survival in UCB patients treated with RC.